2002
DOI: 10.1093/treephys/22.2-3.105
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory potential in sapwood of old versus young ponderosa pine trees in the Pacific Northwest

Abstract: Our primary objective was to present and test a new technique for in vitro estimation of respiration of cores taken from old trees to determine respiratory trends in sapwood. Our secondary objective was to quantify effects of tree age and stem position on respiratory potential (rate of CO2 production of woody tissue under standardized laboratory conditions). We extracted cores from one to four vertical positions in boles of +200-, +50- and +15-year-old Pinus ponderosa Dougl. ex Laws. trees. Cores were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 30 publications
4
45
0
Order By: Relevance
“…For a given diameter, R stem was greater in upper compared to the lower stem positions. R stem is generally greater within or near the crown compared at BH Pruyn et al 2002;Ceschia et al 2002). We also found that over the study period, R stem at BLC was more dynamic than at BH.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…For a given diameter, R stem was greater in upper compared to the lower stem positions. R stem is generally greater within or near the crown compared at BH Pruyn et al 2002;Ceschia et al 2002). We also found that over the study period, R stem at BLC was more dynamic than at BH.…”
Section: Discussionsupporting
confidence: 59%
“…This suggests that R stem at BLC is more closely coupled with canopy metabolism than R stem at BH. Pruyn et al (2002) observed 50% higher rates of both mass-and volume-based respiratory potentials near tree tops in young Pinus ponderosa trees. They suggested that higher rates in the crown were due to the fluxes being measured more proximal to the source of current photosynthate.…”
Section: Discussionmentioning
confidence: 79%
“…More generally, higher rates of smallscale disturbance (e.g., occasional loss of individual leaves to herbivores, fire, or ice) should also reduce maximum tree height. King (1990) argued that a disproportionate increase in stem respiration with height could set maximum tree height, but the data do not support this assumption (Ryan and Waring 1992, Mencuccini and Grace 1996, Pruyn et al 2002. Most wood is truly dead wood, making the energy allocated to tissue construction a far better measure of stem costs than tissue respiration.…”
Section: Dry-mass Allocation Allometrymentioning
confidence: 99%
“…Alternatively, based on the tree structure, the same relation can be derived assuming the total wood maintenance (e w ) is proportional to sapwood volume and that the cross-sectional area of sapwood is proportional to the leaf area above it as in the pipe model (Shinozaki et al, 1964). Empirical studies indicate that the energetic maintenance cost of inner bark is high (Pruyn et al, 2002) and that stem surface area better explains total stem maintenance cost than sapwood biomass or volume (Bosc et al, 2003). This can be caused by both the respiration of the inner bark and increased wood respiration due to closeness of stem surface.…”
Section: Structure Of the New Modelmentioning
confidence: 99%